Health impact assessment and cost‒benefit analysis: Exploring complementarities of methods to assess the impacts of regulations on food consumption - Constanza De Matteu Monteiro; Rodney Feliciano; Jeanne-Marie Membré; Sara Monteiro Pires; Sofie Theresa Thomsen; Stéphan Marette (PLoS ONE, 2025)
This paper proposes an interdisciplinary framework that combines different methodologies to measure the risks and benefits related to dietary patterns and to assess the impact of possible regulations influencing food consumption. First, we briefly review the relevant methodologies within the field of health-economics. Based on the gaps identified in this review, we proposed a framework allowing an integrated application of quantitative health impact assessment (HIA) using disability‒adjusted life year (DALY) and cost‒benefit analysis (CBA) calibrated with measures capturing consumers preferences, such as willingness to pay (WTP) and purchase intent (PI). We applied the framework to a case study focusing on the lentil market to test the feasibility of the methodology and we discuss options for model extensions and their limits. We estimated annual DALYs attributable to an increase in the consumption of lentils (scenarios with or without food substitutions), and measured welfare variations and the impact of regulatory instruments, such as subsidies and taxes. Results showed that a hypothetical increase of 30% or more in the consumption of lentils would not be socially accepted as an immediate market reaction, even if lentils are considered a food substitute to reduce the consumption of unprocessed red meat. Our framework is useful to streamline regulatory interventions as it supports the evaluation of impacts of various regulatory instruments, relevant for policies governing consumers’ awareness or impacting consumers’ choice via incentives. Furthermore, it provides a starting point for further interdisciplinary discussions on holistic assessment supporting food systems change.